Glucagon‐like peptide‐1 receptor agonist regulates fat browning by altering the gut microbiota and ceramide metabolism - Ke Lin; Chunyan Dong; Binyan Zhao; Bailing Zhou; Li Yang (MedComm, 2023)
Abstract Studies have shown that antidiabetic drugs can alter the gut microbiota. The hypoglycemic effects of the drugs can be attributed in part to certain species in the gut microbiome that help the drugs work more effectively. In addition, increasing energy expenditure via the induction of adipose tissue browning has become an appealing strategy to treat obesity and associated metabolic complications. Currently, glucagon‐like peptide‐1 receptor agonist (GLP‐1 RA) treatment for metabolic disorders such as obesity and type 2 diabetes has been widely studied. To determine the mechanism of a long‐acting GLP‐1 RA affects adipose tissue browning and the gut microbiome, we treated high‐fat diet mice with GLP‐1 RA and demonstrated that the drug can regulate adipose tissue browning. 16S rRNA and untargeted metabolomics assays suggested that it increased the abundance of bacterium Lactobacillus reuteri and decreased serum ceramide levels in mice. L. reuteri was negatively correlated with ceramide. We found that the mechanism of ceramide decline was alkaline ceramidase 2 (Acer2) overexpression. Moreover, L. reuteri can play a therapeutic synergistic role with GLP‐1 RA, suggesting that gut microbiota can be used as a part of the treatment of diabetes.